Skiddy, Morris County - Scribner, Eric (Kansas State University, The Chapman Center for Rural Studies, 2011)
There is very little information available pertaining to the disappearing railroad town of Skiddy, located in the extreme northwest corner of Morris County in Kansas. This paper draws from an article in the Council Grove Republican written by a 1936 Kansas State graduate named Don McNeal (“The Old One”). McNeal uncovers the early years of Skiddy in his weekly column “Let It Be Said.” This piece also includes dialogue and pictures provided by Dolly Anderson, a current resident of Skiddy, and Ruby Mann, a former resident and storeowner of Skiddy.
Eric Scribner , “Skiddy, Morris County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/47.
Keywords: Council Grove Republican; Skiddy; Morris County; KATY Railroad; Kaw Indians; Patrick Maloney